Hospitalizations and Mortality of Individuals with Dementia: Evidence from Czech National Registers - Broulikova, Hana Marie; Arltova, Marketa; Kuklova, Marie; Formanek, Tomas; Cermakova, Pavla (Journal of Alzheimer's disease, 2020)
BACKGROUND: Facing an increasing prevalence of dementia, the Czech Republic is developing a new nationwide strategy for the management and prevention of dementia. Lack of evidence about characteristics of individuals with dementia in the country is a major obstacle. OBJECTIVE: The study aimed to 1) characterize individuals with dementia, 2) compare their mortality with the general population, and 3) analyze differences in survival between different dementia disorders. METHODS: The study capitalizes on two nationwide registers in the Czech Republic, from which information about individuals who were hospitalized with dementia or died from it between 1994 and 2014 was retrieved. Standardized intensity of hospitalizations was calculated for each year, mortality was studied using standardized mortality ratio, life-tables, Kaplan-Mayer curves, and Cox proportional hazard models. RESULTS: Standardized intensity of hospitalizations for dementia increased more than 3 times from 1994 to 2014. Standardized mortality ratio was 3.03 (95% confidence interval 2.97-3.08). One-year survival rate was 45% and five-year survival rate 16%. Vascular dementia was the most common type of dementia disorders and was associated with higher hazard of death than Alzheimer's disease, even after adjusting for sociodemographic and clinical covariates (hazard ratio 1.04; 95% confidence interval 1.02-1.05). CONCLUSION: The study provides estimates on demographic characteristics and mortality of the Czech hospitalized dementia population, which have not been so far available and which are unique also in the context of the entire region of Central and Eastern Europe.
Keywords: senioři; proporcionální rizikové modely; Proportional Hazards Models; mortalita; hospitalization; population characteristics; senioři nad 80 let; demence; Alzheimer’s disease; Česká republika; Kaplan-Meier Estimate; registrace; mužské pohlaví; Kaplanův-Meierův odhad; Czech Republic; Registries; Aged, 80 and over; registries; ženské pohlaví; Humans; Mortality; Dementia; Hospitalization; hospitalizace; Female; Aged; mortality; dementia; lidé; Male